DEVELOVING CHARACTER BASED ENGLISH MATERIALS FOR THE NINTH GRADE STUDENTS OF JUNIOR HIGH SCHOOL IN SMP NEGERI 1 PETANG - SUARDANA, I MADE (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2012)
ABSTRACT This study is a Research and Development study (R&D) which aimed at developing character based English material for the ninth grade students of Junior High School in SMP Negeri 1 Petang. The development model used in this study was adapted from the development model by Sugiono (2011). The research was started by analyzing the existing English material used by the teacher and the students of grade IX of SMP Negeri 1 Petang to obtain the weaknesses of the English material being used in the school. The result of the analysis showed that the existing materials suffered from several flaws, such as; the absence of explicit statements about character aspects that need to be included in students? activities, lack of use of clear instructions and examples that supported the clarity of the materials, and the monotonous content and lay-out. These weaknesses were concluded from the result of the questionnaire analysis and observation which found that only 33% the existing materials comply with the teachers? need. Based on the problems, the researcher developed new design of character based English materials which complies with the School Based Curriculum with character building, the criteria of good English material and also the teacher and students? respond through the use of questionnaires. The final product of this research was the character based English material completed with compact disc (CD) for listening material.   Key Words: character building, School Based Curriculum, research & development (R&D)